A dynamic model to sustain the spark: How do network coordinators in Dutch healthcare networks maintain network commitment? - Manon Roest; Doris van der Smissen; Remco Mannak; Leon Oerlemans; Anne Marie Weggelaar-Jansen (PLoS ONE, 2025)
Context In the Netherlands inter-organizational networks have been established to drive long-term healthcare improvement on a regional and national scale. Managing healthcare networks is challenging, especially in sustaining participants’ active engagement. This study aims to empirically explore why participants’ network commitment declined and how network commitment was managed by network coordinators. Methods We conducted an exploratory qualitative study using purposive sampling we held semi-structured interviews with representatives from 18 Dutch healthcare improvement networks. Results Respondents mentioned that allocated time and continued participant commitment was required to reach their goals. A key challenge was the decline in participant commitment over time due to misalignment of goals and needs, slow progress, lack of reciprocity, and resistance to change at the organizational level. Approaches to manage this were collaborative reassessment of goals and needs, expectation management, setting preconditions and fostering personal relationships. Discussion Our findings highlight the importance of strategic timing of managerial approaches and their interdependencies with social mechanisms. These insights contribute theoretically to Ring and Van de Ven’s framework on developmental processes of cooperative interorganizational relationships and offer practical guidance for network managers aiming to maintain long-term commitment.